2016
DOI: 10.1016/j.neuroimage.2016.02.051
|View full text |Cite
|
Sign up to set email alerts
|

The association between cerebrovascular reactivity and resting-state fMRI functional connectivity in healthy adults: The influence of basal carbon dioxide

Abstract: Although widely used in resting-state fMRI (fMRI) functional connectivity measurement (fcMRI), the BOLD signal is only an indirect measure of neuronal activity, and is inherently modulated by both neuronal activity and vascular physiology. For instance, cerebrovascular reactivity (CVR) varies widely across individuals irrespective of neuronal function, but the implications for fcMRI are currently unknown. This knowledge gap compromises our ability to correctly interpret fcMRI measurements. In this work, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 73 publications
6
37
2
Order By: Relevance
“…Moreover, since functional connectivity measures reflect correlated fluctuations in the blood oxygenation level dependent (BOLD) signal, any physiological factors that are known to affect the BOLD signal will also affect measures of functional connectivity (Liu, 2013; Murphy, Birn, & Bandettini, 2013). Vascular health and neurovascular coupling are known to decline with age (D’Esposito, Deouell, & Gazzaley, 2003) and despite attempts to correct for these factors, age differences in resting state connectivity may be at least partly attributable to differences in these non-neural factors (Golestani, Kwinta, Strother, Khatamian, & Chen, 2016). Unlike rest, cognitive tasks include events of interest that can be explicitly modeled and contrasted, allowing for the decoupling of the signal of interest from that of noise and the comparison of relative differences in activation and connectivity across groups and conditions (Buckner, Snyder, Sanders, Raichle, & Morris, 2000; Henson, 2006; O’Reilly, Woolrich, Behrens, Smith, & Johansen-Berg, 2012).…”
Section: What Are Some Of the Limitations Of The Resting State Approach?mentioning
confidence: 99%
“…Moreover, since functional connectivity measures reflect correlated fluctuations in the blood oxygenation level dependent (BOLD) signal, any physiological factors that are known to affect the BOLD signal will also affect measures of functional connectivity (Liu, 2013; Murphy, Birn, & Bandettini, 2013). Vascular health and neurovascular coupling are known to decline with age (D’Esposito, Deouell, & Gazzaley, 2003) and despite attempts to correct for these factors, age differences in resting state connectivity may be at least partly attributable to differences in these non-neural factors (Golestani, Kwinta, Strother, Khatamian, & Chen, 2016). Unlike rest, cognitive tasks include events of interest that can be explicitly modeled and contrasted, allowing for the decoupling of the signal of interest from that of noise and the comparison of relative differences in activation and connectivity across groups and conditions (Buckner, Snyder, Sanders, Raichle, & Morris, 2000; Henson, 2006; O’Reilly, Woolrich, Behrens, Smith, & Johansen-Berg, 2012).…”
Section: What Are Some Of the Limitations Of The Resting State Approach?mentioning
confidence: 99%
“…One important issue is separating the effects of age (or any other variable) on neural versus vascular components of the fMRI signal [Murphy et al, 2013;Tsvetanov et al, 2015]. Functional connectivity estimates, for example, can be confounded by physiological rhythms, such as breathing and heart rate, and different degrees of cerebrovascular reactivity [Golestani et al, 2015[Golestani et al, , 2016Liu, 2013]. This is particularly problematic in the case of aging, given that such rhythms are known to be affected by age.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study found an association between functional connectivity based on fMRI and CVR (Golestani, Kwinta, Strother, Khatamian, & Chen, 2016). A prior study found an association between functional connectivity based on fMRI and CVR (Golestani, Kwinta, Strother, Khatamian, & Chen, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…A prior study found an association between functional connectivity based on fMRI and CVR (Golestani, Kwinta, Strother, Khatamian, & Chen, 2016). It was unclear if this association was due to the spuriously altered fMRI BOLD effect related to the altered blood flow or if it was due to a true decrease in brain connectivity (Golestani et al, 2016;Para et al, 2017). An F I G U R E 4 Scatter plots comparing white matter CVR with the global efficiency and local efficiency of the connectome.…”
Section: Discussionmentioning
confidence: 98%